INTEGRATED AUTOMATION PUMP SEBAGAI ALTERNATIF PENGHEMATAN ENERGI - Putu Oka Sutrisna; I Ketut Sukaya (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2023)
In its implementation, to monitor water discharge to the water treatment section, a flowmeter is used to obtain water discharge results, and an ultrasonic sensor is also added which is connected to the controller which produces height data. Furthermore, water level data, water discharge data and cost rates for water pump motors will be displayed via the website for remote control systems because of the speed of data transmission, efficiency and wide coverage. However, it still needs to be connected to a control device to be able to monitor electrical devices remotely. The research objective is to design an integrated automation pump as an energy saving alternative. The research method using integrated automation pump design using a picobox is power supply circuit design, AC current sensor circuit design, RTC circuit design, and microcontroller circuit design. Based on the research results, based on the results of testing the use of the Lambda Iteration method which is commonly used in economical operations of electric power systems, it turns out that it can also be effectively applied in economical operations using water pump motors. From the results of the calculations that have been carried out, the optimal water pump motor operation scheduling is in the 10th iteration calculation, with the calculation results that the first water pump motor must pump a volume of 59 m3. This scheduling also has an impact on reducing the operating costs of the pump motor which is estimated in one filling cycle to Rp. 6,214,- in one filling cycle. The total energy efficiency of this innovation is 11,880 Kwh/year with cost savings of Rp. 13,068,000. This means that the Lambda Iteration method is able to reduce costs by 34.1%.